2011
DOI: 10.1645/ge-2587.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Osmolality and Selected Ions on Retraction of the Distome Body into the Cercaria Tail Chamber of Proterometra macrostoma (Trematoda: Azygiidae)

Abstract: The furcocystocercous cercariae of the digenetic trematode, Proterometra macrostoma , possess a tail chamber into which their distome body withdraws prior to emergence from their snail intermediate host. The process of distome retraction and the conditions that trigger it in this species are not clear. The objectives of the present study were (1) to describe the retraction process in P. macrostoma; (2) to assess whether osmolality affects cercarial retraction; (3) to evaluate the effect of selected ions on ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…[7][8][9][10][11][12][13][14] Diagnosis of adult based on light microscopy of 7 stained whole mounted specimens. Body of adult orange (live coloration), 1980-2300 (2189, 7) long, 820-1280 (1169, 7) or 1.7-2.7 (1.9, 7)× longer than wide, ventrally concave; tegument approximately 10-20 (14, 7) thick; papillae loosely studding rim of the mouth, tightly encircling the outside rim of the ventral sucker, pored, lacking sensory cilium; tegumental projections (not illustrated) distributed evenly from anterior to posterior end (Fig.…”
Section: Proterometra Epholkos Sp Nmentioning
confidence: 99%
See 3 more Smart Citations
“…[7][8][9][10][11][12][13][14] Diagnosis of adult based on light microscopy of 7 stained whole mounted specimens. Body of adult orange (live coloration), 1980-2300 (2189, 7) long, 820-1280 (1169, 7) or 1.7-2.7 (1.9, 7)× longer than wide, ventrally concave; tegument approximately 10-20 (14, 7) thick; papillae loosely studding rim of the mouth, tightly encircling the outside rim of the ventral sucker, pored, lacking sensory cilium; tegumental projections (not illustrated) distributed evenly from anterior to posterior end (Fig.…”
Section: Proterometra Epholkos Sp Nmentioning
confidence: 99%
“…The latter three species were treated initially by Smith [15,12,21] and all of them require further taxonomic study considering the type materials and based on naturally shed cercariae as well as adults collected from infected, wild-caught fish hosts. Fundamentally problematic is that we could not locate or find reference to an extant type specimen for any species of Proterometra described from Alabama.…”
Section: Proterometra Spp From Alabamamentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, recent osmotic evidence supports a body compartment other than the mantle cavity as the location for P. macrostoma rediae and the site for this distome's body retraction into its cercarial tail. Rosen et al (2011) found significantly more distome bodies retracted into their cercarial tails in artificial snail water (ASW) than in artificial pond water (APW). Presumably ASW more closely approximates the osmolality of this body compartment compared to the osmolality of the mantle cavity.…”
mentioning
confidence: 99%